Towards Improving Road Safety using Advanced Vehicular Networks - Wajeb Gharibi; Nasrullah Armi (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2018)
Vehicular Ad-hoc Networks (VANETs) are advanced network technologies applied to improve safety on roads and to offer suitable solutions for Intelligent Transportation Systems (ITS). The goal of VANETs is to assistdrivers and to act as a smart co-pilot that can alret about accidents and help avoiding them while prodivding high-end infotainment systems for both the driver and passengers. Consequently, VANETs can save millions of lives around the world, especially in Saudi Arabia, which has a very high rate of road accidents annualy. In this paper, we introduce and discuss VANETs, related routing protocols, challenging problems, and the existing solutions. This work is a part of a bigger project that aims to enhance VANETs technologies and to updapteITS to significantly promote road safety in general and Saudi Arabia’s roads in particular.